Guidelines for the Preparation of a Document Containing the Drug Safety Monitoring Results - Yu. V. Olefir; B. K. Romanov; R. N. Alyautdin; S. V. Glagolev (Безопасность и риск фармакотерапии, 2018)
Recommendations for the Marketing Authorisation Holders for the preparation of the document containing the results of the monitoring of safety of the drug, which is presented as part of the dossier at the state registration confirmation in 5 years after the initial registration of the drug in Russia are given. Links to legal documents, and specific examples of the proper execution of the relevant sections of the document are represented.